The Qur’ānic Dialogue with the Mystical Theology of Logos in John’s Gospel - Syed M. Waqas (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2020)
The Qur’ān, the “Holy Writ” of Islam, builds its rationale of revelation on the scriptural model of biblical tradition. Embracing direct divine intervention in worldly affairs as the first principle within the constrictions of monotheistic theology, the Qur’ān resurrects biblical purview of an intermediary agency linking the transcendent divine with the terrestrial human, which the author of John’s Gospel identifies as “Logos”. This article argues that the Qur’ānic conception of kalām-Allah, at a conceptual level, engages with John’s mystical theology of the divine origin of the Logos-incarnate and reinterprets the conception as well as its application. This cornerstone of John’s theology formulates a crucial basis for the Qur’ānic narrator’s self-reflection through both content and form of revelation as such. Biblical literature written prior to Johannine appropriation of Logos does not cohere with John’s mystical paradigm, which the Qur’ān, on the other hand, brings to a whole new level of theological maturation. The Qur’ān dialogues with John’s Gospel at multiple levels on the principal question of God’s personal interaction with humanity and presents its nuanced metaphysical construct in conversation with the Logos principle, but in distinction from John’s incarnation theology.